1995
DOI: 10.1164/ajrccm.151.6.7767529
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A decreases rat skeletal muscle mitochondrial respiration in vitro.

Abstract: Cyclosporine A (CsA) is a potent immunosuppressant used to decrease organ rejection after transplantation surgery. Reported limitations to use of CsA have been hepatotoxicity and nephrotoxicity. Additionally, exercise capacity is much less than expected following transplantation even if arterial oxygen transport capacity is repaired. Purposes of the present study were to determine the effects of CsA on skeletal muscle mitochondrial respiration in vitro and to determine the site of the CsA skeletal muscle mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 13 publications
4
43
2
Order By: Relevance
“…9). Higher concentrations of cyclosporin A had a mild inhibitory effect on ROS generation, possibly through direct inhibition of mitochondrial respiration (57). Thus, there was clearly a component of the ROS generated that was not dependent on opening of the permeability pore, although pore opening may have generated ROS to some …”
Section: Discussionmentioning
confidence: 99%
“…9). Higher concentrations of cyclosporin A had a mild inhibitory effect on ROS generation, possibly through direct inhibition of mitochondrial respiration (57). Thus, there was clearly a component of the ROS generated that was not dependent on opening of the permeability pore, although pore opening may have generated ROS to some …”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin, a calcineurin inhibitor, affects the ability of capillaries supplying skeletal muscle fibres to adequately dilate, thereby reducing oxygen delivery to working muscle [70,79], which could impair the oxidative capacity of exercising muscle. Mitochondrial function may also be impaired in transplant recipients due to a cyclosporin effect on mitochondrial respiration [80,81]. Corticosteroids can also result in muscle fibre atrophy and abnormalities in muscle fibre shape and size [82]; however, the morphological and biochemical changes associated with chronic corticosteroid use are not the same as those observed following LT, making this an unlikely culprit.…”
Section: Exercise Performancementioning
confidence: 99%
“…1 These medications have been shown to have profound effects on cellular features of skeletal muscle in patients with COPD 23,24 and in animals. 25,26 The histology of skeletal muscle and its relationship to muscle function has not been reported in recipients of lung transplants and warrants further examination.…”
Section: Effect Of Immunosuppressant Medications and Deconditioning Omentioning
confidence: 99%
“…Animal studies have shown that cyclosporine in therapeutic doses can decrease the capacity of the electron transport chain (a source of ATP production during oxidative metabolism) by blocking a calcium-dependent pore in the inner mitochondrial membrane, thus affecting calcium efflux from the mitochondria and impairing mitochondrial respiration. 25 This impairment in calcium transport may lead to an inability of working muscle to utilize oxygen and an early shift toward glycolytic metabolism, especially during exercise, resulting in limited exercise capacity. 25,26 Mercier et al 26 reported that the impairment in mitochondrial respiration was associated with reduced endurance time in treadmill running in rats given cyclosporine.…”
Section: Effect Of Immunosuppressant Medications and Deconditioning Omentioning
confidence: 99%